Modelling and simulation of distributed time critical communication and control systems in vehicles or vehicle networks. Issue 3 (2016) - Diekhake, P.; Kurczveil, T.; Becker, U.
Abstract: This paper is dedicated to the methodical analysis of distributed communication and control systems, such like systems inside modern vehicles or systems of networked vehicles. For runtime and time-behavior analyses, the basic models of a communication access and a cycle crossing between program components are discussed. For these sub-problems, exemplary simulation results are shown and validated. Regarding both problems together, a mathematic approach is introduced, which describes the structure of a subsuming process, relevant for time analysis in distributed systems. The simulation of this complete process allows the derivation of realistic statements on the tolerable limits in time critical control systems.